Northern Ireland and the European Union : the dynamics of a changing relationship. - Murphy, Mary C. (Manchester International Relations, 2016)
The most comprehensive coverage to date of the institutional development of Northern Ireland following the UK government's devolution programme and Northern Ireland's development as an autonomous policy actor in Europe.